UJI PERTUMBUHAN DAN PRODUKTIVITAS TANAMAN SAWI MELALUI APLIKASI PUPUK HIJAUAN CLOTALARIA JUNCEA L - Hayun Abdullah; Rahayu Idris; Sugeng Haryanto; Subzan Andi Mahmud (Sekolah Tinggi Pariwisata Mataram, 2022)
Currently, the vegetable products that consumers want are quality and healthy vegetables that are safe for consumption. To get mustard with good quality, it is necessary to increase the application of organic fertilizer, one of which is the provision of forage klotalaria. Green manure is a fertilizer that comes from the weathering of natural ingredients, either the remains of leaves, stems or green fruit. Plant residues in the form of leaves or stover are the most economical sources of organic matter. Clotalaria juncea L is a type of legume that can be used as green manure. On Ternate Island, Clotalaria plants are scattered in various vegetation and open areas. But it has not been used as a source of organic matter among farmers. The purpose of this study was to determine the response of green manure C. juncea L. which was effective on the growth and productivity of mustard plants. The results of the study with a dose of 2 kg of green manure C. juncea L produced a plant height of 32.25 cm, number of leaves 13.25 cm, leaf area of ​​193.9245 cm, and fresh plant weight of 107.5 g, these results were higher than the treatment. other doses.